ANALISIS BIAYA KUALITAS TERHADAP PROFITABILITAS (KASUS PT. PEMBANGUNAN JAYA ANCOL Tbk.) (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2015)
The rapid development of the hospitality industry in particular recreation area is now attracting the interest of entrepreneurs to participate jumped into this business, giving rise to sharp competition. To be able to compete well among a growing number of recreational, PT. Pembangunan Jaya Ancol continue to improve service levels to get the maximum profit.To achieve the level of service PT. Pembangunan Jaya Ancol carry out all the activities of each unit of the service, one way to differentiate a recreational park with more recreational park is to show the high quality of services than its competitors. The key is to match or exceed customer expectations. If the perceived reality in accordance with the desired quality, they will continue to use the services offered by the service providers. Therefore, PT. Pembangunan Jaya Ancol must identify the wishes of consumers in terms of quality. Measurement of the quality, will not escape the inherent quantitative aspects, namely the quality costs (cost of quality).The method used is descriptive method with case study approach in leisure parks PT. Jaya Ancol. This study aimed to determine the application of the cost of quality and profitability levels, so the object of this study are all costs associated with the cost of quality companies. While the unit of analysis in the study used was the financial statements. Pembangunan Jaya Ancol Tbk. the period 2009-2013.Application of the cost of quality has been done by PT. Pembangunan Jaya Ancol Tbk. in the form of: a. Prevention Cost Cost (cost of preparing the design of vehicle travel, marketing costs, the cost of education and training of employees, as well as the cost of printing of paper stationery), b. Fee appraiser appraisal cost (cost of maintaining and controlling equipment tourist rides), c. Internal Failure Cost, d. External Failure Cost).With provision expenses increased then increased profitasbilitasnya. This means that if the company increases the costs (including the cost of quality will improve corporate profitability. This explanation is supported by the percentage increase in profitability was supported by an increase in the cost of companies that have shown that with the increase of 26% in total costs (including the cost of quality), profit will rise 40% to the calculation of 2009 as the basis for calculation.